Editorial: Advances in robotic surgery: innovations, applications, and future directions - Pecorino, Basilio; Maniaci, Antonino; Umile, Annalisa; La Via, Luigi; Zanghì, Antonio (Frontiers in Surgery, 2025)
Robotic surgery has transformed modern operative practice by enhancing precision, dexterity, and visualization far beyond traditional surgical methods. This article explores the evolving integration between robotic surgery and anesthesiology, emphasizing the multidisciplinary nature of perioperative management in technologically advanced environments. As robotic platforms become increasingly intelligent—incorporating artificial intelligence, real-time data feedback, and automation—anaesthetic practice must adapt to new physiological, logistical, and ethical challenges. The development of smart operating rooms and closed-loop anesthesia systems highlights the growing interdependence between surgical and anesthetic processes. Moreover, simulation-based education and interprofessional teamwork are essential to mastering the robotic learning curve and ensuring patient safety. Economic sustainability and ethical governance remain critical as automation and AI reshape surgical responsibility and patient consent. Ultimately, the convergence of robotic systems, anaesthetic innovation, and artificial intelligence defines the future of intelligent perioperative integration, where human expertise and adaptive machine precision cooperate to achieve safer, more efficient, and personalized surgical care.